ANALISIS MUTU PELAYANAN RADIOLOGI TERHADAP KEPUASAN PASIEN RAWAT JALAN DI INSTALASI RADIOLOGI RUMAH SAKIT UMUM AMINAH BLITAR - Kus Endah Aryati (ITKM WIDYA CIPTA HUSADA, 2020)
Satisfaction is the feeling of being happy or disappointed someone who comes from a comparison between his impression of the performance or results of a product and his expectations. Service quality related to satisfaction is determined by five elements that can be known as service quality “RATER” (Reability, Assurance, Tangibles, Emphaty, Responsiveness). Service quality can be defined as the distance between expectations and reality that customers feel for the service they receive. The purpose of this study is to find out the description of the level of satisfaction of outpatients towards health services in the Radiology Installation of Aminah Blitar General Hospital. This study used an observational analytic design conducted with the Cross Sectional method. Aminah General Hospital is one of the Private Hospitals belonging to the Muhammadiyah union. Data collection techniques using the questionnaire method. The service quality questionnaire was 64.66% with the highest dimensions answering satisfied, namely the Assurance dimension of 76.70%. Data collection techniques using the questionnaire method. The service quality questionnaire was 64.66% with the highest dimensions answering satisfied, namely the Assurance dimension of 76.70%.